Thermal performance of ultra-thin flattened heat pipes with composite wick structure - Li, Yong; Zhou, Wenjie; He, Jiabin; Yan, Yuying; Li, Bo; Zeng, Zhixin (Elsevier, 2016)
This study proposes three composite wick structures (copper power or mesh sintered on grooved tube), namely, single arch-shaped sintered–grooved wick (SSGW), bilateral arch-shaped sintered–grooved wick (BSGW), and mesh–grooved wick (MGW), to improve the thermal performance of ultra-thin heat pipes (UTHPs). Phase-change flattening technology is employed to fabricate UTHPs. The morphologies of the wick structures after flattening are observed. An experimental apparatus is setup to investigate the thermal performance of UTHP samples under incremental heat loads. The heat transfer limits of UTHP are theoretically and experimentally analyzed. Capillary limit is found to be the main heat transfer limit, and the theoretical values of the samples with SSGW and BSGW are in good agreement with the experimental results. Results indicate that the maximum heat transport capacities are 12 W, 13 W and 14 W, under the corresponding optimum filling ratios of 70%, 70%, and 80%, for the SSGW, BSGW and MGW UTHPs, respectively. Evaporation and condensation thermal resistances of UTHP samples increase with the increase in the filling ratio before the occurrence of dry-out. UTHPs with SSGW have the least evaporation thermal resistance whereas UTHPs with MGW have the least condensation thermal resistance.